Dusinvare : Avgangsutstilling 1993 : 12 studenter fra Vestlandets Kunstakademi. - Bergens Kunstforening, Bergen (Bergen : Vestlandets Kunstakademi, 1993)
Bjerkreim, Kari ; Borresen, Tor ; Fredriksen, Sissel ; Iden, Trond ; Ingvaldsen, Arne ; Lien, Gunnhild ; Lindo, Lidunn ; Sivertsen, Kari ; Snedsbol, Erik ; Stromnes, Anne Britt ; Tverbakk, Per Gunnar ; Aanestad, Marit
Dusinvare : Avgangsutstilling 1993 : 12 studenter fra Vestlandets Kunstakademi, Bergens Kunstforening, 1993
boek